Encapsulation of Canola Oil by Sonication for the Development of Protein and Starch Systems: Physical Characteristics and Rheological Properties - Silva Paz, Reynaldo J. (2025)
Canola oil, extracted from Brassica napus, is appreciated for its nutritional profile, but its use in the food industry is limited by its susceptibility to oxidation. This study aimed to evaluate the nanoemulsion of canola oil by sonication to develop stable nanoemulsified gels from protein and starch systems. Two stages were performed. In the first stage, oil-in-water (O/W) nanoemulsions were prepared using soy lecithin and Tween 80 as emulsifiers, analyzing their physical stability by particle size and polydispersity index. The results show that the sonication conditions and emulsifier concentration significantly affected the creaming index and particle size. In the second stage, gels were developed from these nanoemulsions, evaluating their colorimetric and rheological properties. It was observed that the gels presented a viscoelastic behavior suitable for food applications, with a higher luminosity in protein systems. In conclusion, nanoemulsion by sonication improves the stability of canola oil, suggesting its potential use in various food applications. Additional emulsifier combinations and optimization of processing conditions are recommended to further improve the stability and functionality of the encapsulated oil.